固相萃取净化-超高效液相色谱-串联质谱法同时测定 食用植物油中大麻酚、大麻二酚和Δ9-四氢大麻酚Simultaneous determination of cannabinol, cannabidiol and Δ9-tetrahydrocannabinol in edible vegetable oil by solid-phase extraction purification coupled with ultra performance liquid chromatography-tandem mass spectrometry - 许晴1,2，毛燕妮1,2，康翠欣1,2，高盼3，杨永1,2 XU Qing1,2, MAO Yanni1,2, KANG Cuixin1,2, GAO Pan3, YANG Yong1,2 (Zhongguo youzhi, 2024)
为有效提高食用植物油中大麻素类化合物的风险监测水平，建立一种固相萃取净化-超高效液相色谱-串联质谱同时测定食用植物油中的大麻酚、大麻二酚和Δ9-四氢大麻酚的方法，并通过方法检出限、定量限、不确定度、加标回收率和精密度等对该方法的准确性进行了验证。结果表明：在以5 mL乙腈提取两次、EMR-Lipid固相萃取柱为净化柱、水和甲醇为流动相梯度洗脱、Agilent Pursuit 3 PFP色谱柱（3 μm，2.0 mm×150 mm）分离，负离子模式下电离、多反应模式监测、基质标准曲线同位素内标法定量条件下，大麻酚、大麻二酚、Δ9-四氢大麻酚在5~200 ng/mL质量浓度范围内均呈现良好的线性关系，检出限均为10 μg/kg，加标回收率为84.27%~100.30%，相对标准偏差为1.2%~3.9%；实际样品测定中发现部分食用植物油中存在大麻素类化合物。该方法操作简单、快速、准确度高，适用于食用植物油中大麻酚、大麻二酚、Δ9-四氢大麻酚的测定。In order to effectively improve the risk monitoring level of cannabinoid compounds in edible vegetable oils, a method for the simultaneous determination of cannabinol, cannabidiol and Δ9-tetrahydrocannabinol in edible vegetable oils by solid-phase extraction purification coupled with ultra performance liquid chromatography-tandem mass spectrometry was established, and the accuracy of the method was verified by the limit of detection, limit of quantification, uncertainty, spiked recovery and precision. The results showed that the extracts were extracted twice with 5 mL acetonitrile, purified by an EMR-Lipid-type solid-phase extraction column, eluted with a gradient of water and methanol as the mobile phases, and separated on an Agilent Pursuit 3 PFP (3 μm, 2.0 mm×150 mm) type column, with ionisation in the negative ion mode, monitored by the multiple reaction mode, and quantified by isotopic internal standard method in the matrix standard curve. Under the conditions of this method, cannabinol, cannabidiol and Δ9-tetrahydrocannabinol showed good linearity in the mass concentration range of 5-200 ng/mL, and the limits of detection were all 10 μg/kg, with the spiked recoveries ranging from 84.27% to 100.30% and the relative standard deviations of 1.2%-3.9%; the presence of cannabinoids was detected in the determination of some edible vegetable oils in the actual samples. The method is simple, rapid, accurate and suitable for the determination of cannabinol, cannabidiol and Δ9-tetrahydrocannabinol in edible vegetable oils.